Assessing the impact of Regional Integration and International Trade on Economic Growth and Food Security in ECOWAS (Global Journal of Management and Business Research, 2018)
This study analyzes the potential of regional integration through the potential of global value chains in accelerating economic growth and achieving food security with a focus on ECOWAS. Some strategies that regional integration can promote to stimulate economic growth and increase food security are compared. This study examines whether countries must develop strategies to raise international trade through increasing openness degree or whether countries must develop policies to reinforce community or regional trade through the potential of value chains inside the regional integration. Three instruments are investigated (trade openness, intraregional trade and the community insertion to value chains). Two models are estimated with panel fixed effects using data from 1995 to 2012. The findings support that regional integration needs to be strengthen and better promoted in order to stimulate the potential of each country to move from discontinuous growth to sustained growth. International trade is not the better solution for ECOWAS countries to boost economic growth but regional trade linked to creation of value chains among each country can be the engine of the region growth and food security.
Keywords: food security; economic growth; trade openness; regional integration; value chains